Gender Sensitive and Gender Neutral Language: The Word-World Nexus and Its Fluctuations - Stefanović, Tamara M.; Spasić, Dragana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The article focuses on the relationship between language and gender. It explores the ways in which the link between them is reflected in and reflects the socio-political dynamics. It delineates the thematic framework for the constructive debate, rather than proposing solutions for the social unease. The historical perspective brings to awareness the evolution of diverse occurrences of feminism and how they have fashioned the language through which the contested social realm is expressed. Voices from the social margins nowadays claim the language that embodies antidiscrimination politics and mirrors their identity. Transgender activists have raised the question of gender neutral language. Simultaneously, similar demands come from a different standpoint. How is one to understand those points of ‘convergence’? Confronted with such a complex situation, one wonders whether diversified discourse reflects atomized society. One may also ask if it spurs the dispersal of the social. By contrast, one would like to know if it perhaps reverberates with and inspires the blossoming of pluralist culture and linguistic playfulness it can ensure. One wonders how we can both exercise and discuss antidiscrimination politics, and avoid the bewilderment that the fluctuations of the world-word nexus sometimes cause. Moreover, the question of immense importance is how we can avoid hypocrisy while trying to harmonize discourse and the social sphere. The overarching question seems to be how we can generate a sound community of human beings in which language is the means of vibrant communication.